DISENTANGLING CLIMATIC AND INTRINSIC PHYSICOCHEMICAL CONTROLS ON ORGANIC CARBON POOLS OF AGRICULTURAL SOILS ALONG A CLIMATE GRADIENT - Faiza Anwar; Faisal Mahmood; Sabir Hussain; Muhammad Sanaullah; Tanvir Shahzad (Journal of Animal and Plant Sciences, 2025)
Recently, physicochemical properties of soils are emerging as an equally important control on soil organic carbon (SOC) pools as climatic factors. However, the same needs to be established across biomes and soil types to generalize the emerging paradigm. We sampled 21 agricultural soils from a climate gradient of humid to arid covering ~1600 km distance between 28.02º-35.8º N in Pakistan. An array of soils’ physicochemical characteristics was determined in addition to various SOC pools. Backward stepwise regression, correlation matrix, and principal component analysis were performed to link climatic and soils’ physicochemical variables with SOC pools. When controlled for soil’s physicochemical properties, climatic variables did not show any significant relationship with any of the SOC pools. However, physicochemical properties of soil like clay content, calcium (Ca2+) and magnesium (Mg+2) ions, and total reserve in base cations (TRB) were found in a strong positive relationship with SOC content and stocks as well as stable SOC fractions. Moreover, as the SOC content of a soil increased, living part of the SOC i.e., microbial biomass also increased while its mineralizable fraction decreased. On the other hand, an increasing pH resulted in higher SOC mineralization and lower SOC content and stocks. Overall, these results indicate that the clay particles, and their component base minerals protect the SOC through aggregation and by making organo-mineral complexes. In conclusion, we show that climatic variables mean annual temperature (MAT) and mean annual precipitation (MAP) were not found strongly linked with any of the SOC pools across a large gradient of soil’s intrinsic physicochemical properties. However, across a large gradient of climatic variables, soil’s physicochemical properties were found to strongly control SOC and its pools. Specifically, clay particles and total reserve in base cations were found to be key determinants of SOC.
Keywords: Soil organic carbon (SOC); SOC fractionation; mean annual temperature; mean annual precipitation; microbial biomass; soil respiration